A high selective tri-band bandpass filter with switchable passband states. Issue 2 (15th August 2019) - Bandyopadhyay, Anjan; Sarkar, Pankaj; Mondal, Tapas; Ghatak, Rowdra
Abstract: A new class of switchable bandpass filter using PIN diodes is presented in this paper. The design aims at achieving a multistate switchable bandpass filtering characteristics between the passbands centered at 2.4, 3.5, and 5.2 GHz. The proposed filter is designed by assembling two λ g /2 open-ended and four short-ended λ g /4 uniform impedance resonators. The open-ended resonator generates a fixed passband at 3.5 GHz, whereas the short-ended resonators loaded with PIN diodes are independently controlling the ON and OFF characteristics of the passband centered at 2.4 and 5.2 GHz. The transmission zeros around each passband are produced without employing any additional circuit. The filter sample is fabricated and tested for experimental verification. A good agreement has been observed between EM-simulated and measured results. The designed filter has a compact size of 0.20 λ g × 0.15 λ g at 2.4 GHz.